Improving Students’ Ability in Writing Recount Text by Using the Characters in the Films - Lestiyanawati, Rochyani (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
The students of EFL Classroom sometimes find difficulty in writing. The students difficulty in writing caused by the gate between the students’ L1 and L2 and the lack of supported information related to the source of idea for writing. Teaching media are to solve the problems especially in writing. This study is aimed at using films, especially the characters, as media in improving students’ ability in writing recount. The subject of the study were 30 numbers of 10th graders of vocational school students. The findings showed that the average of the pre-test and post-test scores were 67.53 and 83.63. The improvement calculation was found 0.496 which was categorized as medium. The calculation of applying the t-test was on rejection area of ??Ho, showed that the post-test was better than the pre-test. According to the data analysis, the writer concludes that the strategy by using films is applicable since it helps students to solve their problem in writing recount. The media enable the students to actively engage to the learning process and improve their ability in writing for they give them the idea of writing recount.